Profil Kemampuan Matematika Anak Usia Dini Melalui Learning to Think Different - Titin Faridatun Nisa'; Muhammad Busyro Karim (PG-PAUD Trunojoyo, 2017)
This study aims to determine the profile of early childhood math skills in learning to think different. The type of this research is explorative research with qualitative approach. This research results will be analyzed by using qualitative analysis. The results showed that the profile picture of early childhood math ability in the group of children with below average ability had similarities with the average group in logical and symbolic thinking ability with the categories evolving as expected. As for the ability to think critically the same, that category began to grow. A group of children with below average skills has problem-solving skills with the category beginning to develop, while the group of children with average ability including the category evolves according to expectations.